The relationship between individualised speed thresholds and changes in aerobic fitness in elite professional youth soccer players. A case study - Kavanagh, R.; McDaid, K.; Rhodes, D.; Alexander, J.; Harper, D.; Oliveira, R.; Berry, K.; Connor, M.; Zmijewski, P.; Morgans, R. (Baltic Journal of Health and Physical Activity, 2025)
Background: This study aimed to examine the dose-response relationship between training load and aspects of physical fitness in English Premier League (EPL) U23 soccer players. Materials and Methods: Seven male EPL U23 outfield soccer players (age 20.1±1.1 years) participated in this study and performed the Bronco test on five occasions within one season. Individualised running thresholds were employed using maximal aerobic speed (MAS), anaerobic speed reserve (ASR) and maximal sprint speed (MSS) values utilising a GPS system. Results: No significant differences in the Bronco performance between the tests (p > 0.05, ES = 0.101) were observed. Distance covered above 30% ASR (r = -0.51) and time spent above 30% ASR (r = -0.54) over a 2-week period displayed a moderate negative linear relationship with Bronco performance. Conclusions: ASR-based training load variables displayed the highest correlations with Bronco results. These findings support practitioners to individualise high-speed running thresholds.